Pseudomonas uvaldensis sp. nov., a bacterial pathogen causing onion bulb rot. Issue 4 (20th April 2022) - Khanal, Manzeal; Timilsina, Sujan; Bhatta, Bed Prakash; Bophela, Khumbuzile; Coutinho, Teresa; Cochran, Kimberly; Malla, Subas
Abstract : A Gram-stain-negative, aerobic and non-spore-forming bacterial strain, designated 20TX0172 T, was isolated from a rotting onion bulb in Texas, USA. The results of phylogenetic analysis based on the 16S rRNA sequence indicated that the novel strain represented a member of the genus Pseudomonas and had the greatest sequence similarities with Pseudomonas kilonensis 520-20 T (99.3 %), Pseudomonas corrugata CFBP 2431 T (99.2 %), and Pseudomonas viciae 11K1 T (99.2 %) but the 16S rRNA phylogenetic tree displayed a monophyletic clade with Pseudomonas mediterranea CFBP 5447 T . In the phylogenetic trees based on sequences of four housekeeping genes ( gap1, gltA, gyrB and rpoD ), the novel strain formed a separate branch, indicating that the strain was distinct phylogenetically from known species of the genus Pseudomonas . The genome-sequence-derived average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) values between the novel isolate and P. mediterranea DSM 16733 T were 86.7 and 32.7 %, respectively. These values were below the accepted species cutoff threshold of 96 % ANI and 70 % dDDH, affirming that the strain represented a novel species. The genome size of the novel species was 5.98 Mbp with a DNA G+C content of 60.8 mol%. On the basis of phenotypic and genotypic characteristics, strain 20TX0172 T represents a novel species of the genus Pseudomonas . The name Pseudomonas uvaldensis sp. nov. is proposed. The type strain is 20TX0172 T (=NCIMB 15426 T =CIP 112022 T ).